Preservation of Interference Effects in Working Memory After Orbitofrontal Damage - Llorens, Anaïs; Funderud, Ingrid; Blenkmann, Alejandro O.; Lubell, James; Foldal, Maja; Leske, Sabine; Huster, Rene; Meling, Torstein R.; Knight, Robert T.; Solbakk, Anne-Kristin; Endestad, Tor (Frontiers in Human Neuroscience, 2020)
Orbitofrontal cortex (OFC) is implicated in multiple cognitive processes, including inhibitory control, context memory, recency judgment, and choice behavior. Despite an emerging understanding of the role of OFC in memory and executive control, its necessity for core working memory (WM) operations remains undefined. Here, we assessed the impact of OFC damage on interference effects in WM using a Recent Probes task based on the Sternberg item-recognition task (1966). Subjects were asked to memorize a set of letters and then indicate whether a probe letter was presented in set. Four conditions were created according to the forthcoming response (‘yes’ / ‘no’) and the recency of the probe (presented in the previous trial set or not). We compared behavioral and EEG responses between healthy subjects (n=14) and patients with bilateral OFC damage (n=14). Both groups had the same recency pattern of slower reaction time when the probe was presented in the previous trial but not in the current one, reflecting the proactive interference. The within-group electrophysiological results showed no condition difference during letter encoding and maintenance. In contrast, ERPs to probes showed distinct within-group condition effects, and condition by group effects. The response and recency effects for controls occurred within the same time window (300-500 ms after probe onset) and were observed in two distinct spatial groups including right centro-posterior and left frontal electrodes. Both clusters showed ERP differences elicited by the response effect, and one cluster was also sensitive to the recency manipulation. Condition differences for the OFC group involved two different clusters, encompassing only left hemisphere electrodes and occurring during two consecutive time windows (345-463 ms and 565-710 ms). Both clusters were sensitive to the response effect, but no recency effect was found despite the behavioral recency effect. Although the groups had different electrophysiological responses, the maintenance of letters in WM, the evaluation of the context of the probe, and the decision to accept or reject a probed letter were preserved in OFC patients. The results suggest that neural reorganization may contribute to intact recency judgment and response after OFC damage.